Hubungan Motivasi Belajar Bahasa Asing Dengan Tingkat Kecerdasan Emosional Para Santriwati SMA Darul Hijrah Puteri - Hartina, Siti; Sagir, Ahmad; Hairina, Yulia (Islamic Psychology Study Program, Faculty of Ushluddin and Humanities, UIN Antasari Banj, 2022)
This study aims to determine the relationship between motivation to learn Arabic and English with the level of emotional intelligence of the students of SMA Darul Hijrah Puteri Cindai Alus Martapura. This type of research is a correlation with a quantitative approach. The population in this study were Santriwati SMA Darul Hijrah Puteri from grade 1 to grade 3 SMA from both the Intensive and TMI classes. The sampling technique used is Probability Sampling. The sample of this study amounted to 174 people. Based on the research conducted, the results obtained are: 1) The level of motivation to learn a foreign language in the high category is 26 people (14.9%), moderate 126 people (72.4%) and low 22 people (12.6%). 2) The level of emotional intelligence in the high category as many as 33 people (19.0%), medium 114 people (65.5%) and low 27 people (15.5%). 3) There is a relationship between motivation to learn foreign languages and the level of emotional intelligence the female students of SMA Darul Hijrah Puteri with a significance value of 0.003 (sig < 0.05) and an effective contribution of 5.1%